Macrocyclic alkanes in crude oils from the algaenan of Botryococcus braunii - Audino, Michiele; Grice, Kliti; Alexander, Robert; Kagi, Robert (Pergamon-Elsevier, 2002)
New classes of biomarkers, macrocyclic alkanes, have been previously identified in high grade oil shales (torbanites, Late Carboniferous-Late Permian) containing remains of the freshwater alga Botryococcus braunii (B. braunii). In this study we report the occurrence of these compounds in two Indonesian crude oils (Minas and Duri, Tertiary) utilising metastable reaction monitoring GC?MS experiments. Based on 13C data and the distributions of the macrocyclic alkanes we suggest that the macrocyclic alkanes are likely formed by an olefin metathesis reaction of a structurallyspecificpolyunsaturated precursor i.e. the algaenan of B. braunii. The macrocyclic alkanes appear to be novel markers of B. braunii and add to the catalogue of the characteristic hydrocarbons derived from this alga. More importantly, these components could be original markers specific to the highly resistant algaenan of B. braunii in sediments and crude oils, unlike n-alkanes which can have multiple origins.